If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 10 = 2 Reorder the terms: 10 + n = 2 Solving 10 + n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + n = 2 + -10 Combine like terms: 10 + -10 = 0 0 + n = 2 + -10 n = 2 + -10 Combine like terms: 2 + -10 = -8 n = -8 Simplifying n = -8
| F(x)=6x-x^2+8 | | 9b^2-27b+18=0 | | 5+5b-3=2+5b | | -4w-7k=28fork | | 5x-6=3x-6+2x | | ln(8x)=3.9 | | 3t+7=3t+6 | | 5h^2+8h-85=0 | | (Y-9)-(Y+3)=5Y | | 13x-3x=2x+3 | | 5x=10-3[2x-5(x+8)] | | (Y-7)-(Y+4)=10Y | | 6x+11=12-7x | | X+2x=50+90+10 | | p-10=-10 | | y-3=6(x+1) | | 3(4m-5)=124m | | 2*x+1=2+2x | | (15b-1)-7(2b+2)=-6 | | 7x+4x+3+9=6x+3+4x | | x+7*2=3x+5 | | 10b+3+4= | | 12-7x=6x+11 | | 96+122=180 | | x+(x-48700)=284790 | | f(4)=10-.25*4 | | -9+5x=-9 | | 7x+5=7-7x | | 6x+12=-28-4c | | 7x^2+6=17x-5 | | 6x+9+7y-2x+3= | | 8+6x=-22+x |